Benson Relaxation Therapy reduces stress levels among undergraduate students during thesis writing - Hafnidar, Hafnidar; Adelia, Dyotami; Irza, Dwi; Eliana, Dea; Rani, Guatia (INSPIRA: Indonesian Journal of Psychological Research, 2025)
Thesis completion represents a significant source of academic stress for final-year undergraduates. This study examined the effect of Benson Relaxation Therapy (BRT) as a non-pharmacological intervention on stress levels among students completing their thesis at Universitas Malikussaleh. A quantitative, experimental design was employed using a posttest-only approach. Of the 30 initial respondents screened, three students with high stress levels participated in the BRT intervention. Stress was measured using an adapted questionnaire based on Sarafino and Smith’s (2012) model. Quantitative inferential analysis indicated no statistically significant effect of the intervention (p = .626). However, observational data from the intervention group indicated favorable subjective and behavioral changes, including reduced anxiety, a more tranquil disposition, and decreased physiological arousal following the session. While the small sample size limits statistical generalizability, the qualitative findings suggest BRT may hold practical value as a simple, culturally adaptable stress management tool. The study points out that further research with more rigorous methodologies, including larger samples and pretest-posttest designs, is needed to conclusively evaluate the efficacy of BRT in academic settings. These preliminary results contribute to the growing literature on holistic, non-pharmacological approaches to supporting student mental health during demanding academic transitions